COVID-19 pandemic - A review and assessing higher education institution undergraduate student’s mental health - Mohd Amiruddin Mohd Kassim; Pang, Nicholas Tze Ping; James, Sandi (Penerbit UMS, 2020)
Introduction: The current COVID-19 pandemic has sequelae reverberating around Malaysia, particularly in university students, as Malaysian university students are isolated in their university campuses in semi-quarantine status. This article seeks to review the existing literature on the specialized issue of university student-related psychological sequelae of COVID-19, and seeks to offer some recommendations through the process. Methods: Existing literature demonstrates that COVID-19 has affected university students psychosocially, with the rate of anxiety and depression markedly increased. There have been significant alterations of lifestyle related to education, in accordance with the new normal, resulting in isolation and feelings of disengagement with education. Moreover, with the current uncertainties regarding their studies and possible financial depression post-pandemic, the future is deeply worrying and will adversely affect their mental health. Results: Quantitatively, recent findings indicate 33.3% of the undergraduates in a higher education institution are noted to be in stress. Therefore, multiple interventions have been implemented; a customized ultra-brief psychological module, an online tele psychiatry hotline (COVID Cares) and tele-counselling, which have received universally positive feedback. Conclusion: In conclusion, the review demonstrates that undergraduates’ psychological health is an aspect that needs urgent attention as it is not merely limited to the fear of COVID-19, but also related to the social aspects of the pandemic. Multiple interventions have been seen to be efficacious in reducing the psychological sequelae.